Part A:
4x + 2(x - 3) = 4x + 2x - 11
4x + 2x - 6 = 4x + 2x - 11
6x - 6 = 6x - 11
6x - 6x = -11 + 6
0 = -5
Since 0 is not equal to -5, the equation has no solutions.
Part B:
One property used to solve this equation is the Distributive Property, where we distributed the coefficient 2 to both terms inside the parentheses on the left side of the equation.
An equation is shown below:
4x + 2(x − 3) = 4x + 2x − 11
Part A: Solve the equation and write the number of solutions. Show all the steps. (6 points)
Part B: Name one property you used to solve this equation. (4 points)
Explain in 1 sentence
1 answer